In-situ Monitoring of the Out-Of-Autoclave Consolidation of Carbon/Poly-Ether-Ketone-Ketone Prepreg Laminate - Saffar, Florence; Sonnenfeld, Camille; Beauchêne, Pierre; Park, Chung Hae (Frontiers in Materials, 2020)
The main objectives of this article were to examine the feasibility of high quality laminate (carbon PEKK – Poly-Ether-Ketone-Ketone) manufacturing under low pressure and to analyze the principal phenomena governing the consolidation quality. The quality of laminate was evaluated in terms of the interlaminar shear strength measured by short-beam test and the residual voids observed by micrographic images. This work underlined the possibility to obtain a good interlaminar consolidation quality under a low pressure of 0.7 bar even for prepregs which were not designed for out-of-autoclave processes. To better understand the interlaminar consolidation phenomena, we developed an experimental set-up for the in-situ monitoring of the laminate consolidation to measure the change of laminate thickness and the temperature gradient in the thickness direction during the manufacturing process. Indeed the in-situ monitoring of temperature gradient through the laminate thickness is an effective way to observe the consolidation phenomena. In particular, we identified two major phenomena, the establishment of intimate contact between the adjacent layers at the glass transition temperature and the molten matrix flow at the melting temperature. The assumption on the intimate contact establishment at the glass transition temperature was confirmed by the heat transfer simulation considering the change of thermal contact resistance at the interlaminar interface.